2011
DOI: 10.1111/j.1462-5822.2011.01714.x
|View full text |Cite
|
Sign up to set email alerts
|

The cooperative action of bacterial fibronectin-binding proteins and secreted proteins promote maximal Campylobacter jejuni invasion of host cells by stimulating membrane ruffling

Abstract: Summary This study was performed to elucidate the host cell scaffolding and signaling molecules that Campylobacter jejuni utilizes to invade epithelial cells. We hypothesized that the C. jejuni fibronectin-binding proteins and secreted proteins are required for cell signaling and maximal invasion of host cells. C. jejuni binding to host cells via the CadF and FlpA Fibronectin-binding proteins activated the epidermal growth factor (EGF) pathway, as evidenced by inhibitor studies and immunoprecipitation coupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
144
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(152 citation statements)
references
References 47 publications
8
144
0
Order By: Relevance
“…119 For instance, the bacterial fibronectin-binding protein of Campylobacter jejuni, CadF, and the intact flagellum are involved in eukaryotic Rac1 GTPase activation and host cell invasion. 116,120 It has been postulated that CadF binding to fibronectin results in integrin clustering and activation. These events lead to the activation of signaling cascades that involves epidermal growth factor receptor (EGFR) and focal adhesion kinase (FAK), resulting in association of c-Src and phosphorylation of paxillin.…”
Section: Treponema Pallidummentioning
confidence: 99%
See 1 more Smart Citation
“…119 For instance, the bacterial fibronectin-binding protein of Campylobacter jejuni, CadF, and the intact flagellum are involved in eukaryotic Rac1 GTPase activation and host cell invasion. 116,120 It has been postulated that CadF binding to fibronectin results in integrin clustering and activation. These events lead to the activation of signaling cascades that involves epidermal growth factor receptor (EGFR) and focal adhesion kinase (FAK), resulting in association of c-Src and phosphorylation of paxillin.…”
Section: Treponema Pallidummentioning
confidence: 99%
“…Finally, the recruitment of Dock180, a Rac1-specific guanine nucleotide exchange factor, provokes the activation of Rac1, leading to a local restructuring of the actin cytoskeleton and the engulfment of the bacteria. 116,120 Similarly, in infections caused by T. pallidum, the bacterial adhesins might target fibronectin and laminin not only to enhance the binding to host cells [108][109][110] but also to trigger intracellular signaling pathways that might promote Rac1 activation and consequently actin remodelling at the attachment site, facilitating the invasion of host tissues. Nevertheless, the role of Rho GTPases and the actin cytoskeleton in treponemal infections remains almost unexplored.…”
Section: Treponema Pallidummentioning
confidence: 99%
“…However, the exact function of CiaB is still not clear. In addition, C. jejuni adherence to cells has been shown to involve a variety of different outer membrane adhesins, including JlpA, PEB1 and the fi bronectin binding proteins CadF and FlpA [14][15][16][17]. Campylobacter jejuni invasion of INT-407 and other cell lines has been observed to induce rearrangements of the host cytoskeleton by small Rho GTPases, which are directly linked to bacterial uptake [18].…”
Section: Introductionmentioning
confidence: 99%
“…Campylobacter jejuni invasion of INT-407 and other cell lines has been observed to induce rearrangements of the host cytoskeleton by small Rho GTPases, which are directly linked to bacterial uptake [18]. Various lines of evidence indicated that the GTPase members, Rac1 and Cdc42, but not RhoA, are activated during infection and play a signifi cant role in the invasion process [17,18]. The detailed signaling pathways leading to the activation of Rac1 and Cdc42 involve CadF targeting of fi bronectin and require certain receptors (integrins, EGF and PDGF receptors), kinases (FAK, Src, and PI3-kinase) and guanine exchange factors (DOCK180, Vav2, and Tiam-1).…”
Section: Introductionmentioning
confidence: 99%
“…Flagellar motility has been shown to be important in invasion (85), as has the fibronectin-binding protein CadF, which was re-cently shown to be involved in host cell membrane ruffling (19). As with colonization, work investigating fundamental aspects of C. jejuni physiology and stress survival has also revealed roles for these properties in invasion and/or intracellular survival.…”
mentioning
confidence: 99%